Asuhan Keperawatan Pada Pasien Halusinasi Pendengaran Dengan Penerapan Terapi Aktivitas Menggambar Di Ruangan Mandau 2 RSJ Tampan Provinsi Riau - Windi Okdwi Delta Maulina; Rina Herniyanti; Ifon Driposwana Putra; Fitry Erlin (Jurnal Sains Farmasi Dan Kesehatan, 2025)
The impact that can be caused by patients experiencing auditory hallucinations is a loss of self-control. Patients experience panic and their behavior is controlled by their hallucinations. In this situation, patients can commit suicide, kill others (homicide), and even damage the environment. To minimize the impact of hallucinations, appropriate hallucination treatment is needed. One way to manage hallucinations is through generalist therapy and drawing activities. Drawing activity therapy aims to minimize the patient's interaction with their world, express thoughts, feelings, and emotions that influence behavior, provide motivation and happiness, entertain and distract the patient, so that attention is not focused. The purpose of this study is to provide therapy for patients with auditory hallucinations using drawing activity therapy. The method used in this scientific work is drawing therapy intervention. The sample of this study was 1 schizophrenia patient with a nursing diagnosis of auditory hallucinations. The study was conducted on April 24-26, 2025. The results showed that after drawing therapy on the third day, the patient said that sometimes he still heard whispers but the voices had decreased and the patient said he wanted to go home immediately.